MENINGKATKAN KEMANDIRIAN LULUSAN DAN MAHASISWA MELALUI PELATIHAN PERAWATAN LUKA KRONIS PENDERITA DIABETES - Sutriyanti, Yanti; Mulyati, Leli; Haryani, Sri; Buana, Chandra (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2025)
The independence of nurse graduates in working is an important concept to pay attention to so that nurse graduates are ready to work after completing college. Nurse graduates at the Bengkulu Ministry of Health Polytechnic are absorbed as overseas workers or as workers in the capital or other provinces. However, there are still 33% working as honorary workers in their own place. The large number of DM cases in Rejang Lebong district that experience wound complications provides an opportunity for graduates and students to carry out competent chronic wound care so that they can work as diabetes chronic wound nurses. The aim of this community service is to improve chronic wound care skills, especially for graduates and students so they can apply their skills independently in the community. The method of activity carried out was wound care training which was held on September 5 2024. There were 25 training participants consisting of graduates and students. The results of this training were an increase in knowledge and skills in caring for chronic diabetes wounds before and after being given the training with an average increase in knowledge of 4.76. From the results of observations of wound care practices, all participants were able to carry out wound care practices in accordance with standard SOPs for caring for chronic diabetes wounds. Training participants received a wound care certificate from the PPNI organization. Training monitoring was carried out by supervision of the community service team when carrying out home care and as many as 44% of participants had carried out wound care in the community. Key words: Training, Wound Care, Diabetes Mellitus